Creating value through product-service-software systems in institutionalized ecosystems – The case of autonomous ships - Tsvetkova Anastasia; Hellström Magnus; Ringbom Henrik (Elsevier, 2022)
Introducing product-service-software systems (PSSS) to the market requires forming an enabling ecosystem, which can be largely based on incumbent business ecosystems. Creating value through PSSS with autonomous capabilities will likely encounter numerous challenges related to the lock-ins in current ecosystem structure. We use institutional theory as a lens and autonomous ships as the case to shed some light on types and impacts of these barriers. We identify a set of institutional barriers pertinent to regulatory, normative and cultural-cognitive pillars of institutions. We further analyze how institutional barriers affect creating, delivering, and capturing value of autonomous ships, ultimately shaping the ecosystem formation around PSSS. The main contribution of the paper is the depiction of early ecosystem dynamics as the mutual adaptation of the PSSS value proposition and the structure of the incumbent ecosystem.